Penetapan Kadar Vitamin C dan Aktivitas Antioksidan Hasil Perasan Buah Jambu Biji Kristal - Melinda, Reni; Sartika Daulay, Anny; Ridwanto, Ridwanto; Amin Nasution, Muhammad (Indonesian Journal of Pharmaceutical Education, 2024)
Vitamin C or ascorbic acid, is a type of water-soluble vitamin derived from hexose. Ascorbic acid contains a chromophore group, which is sensitive to light or forms of electromagnetic radiation. In addition, ascorbic acid functions as an antioxidant and protector against free radicals. Vitamin C is an antioxidant vitamin that can ward off various extracellular free radicals. This antioxidant property comes from the -OH groups number 2 and 3 which are bound to the C atom with a conjugated double bond so that they can donate hydrogen ions to various oxidant compounds, such as free radicals. This study aims to determine the content of secondary metabolites from crystal guava juice (psidium guajava L.), to determine the levels of Vitamin C (psidium guajava L.), and to conduct antioxidant activity tests on crystal guava juice (psidium guajava L.). The stages of this study include sample processing, phytochemical screening, qualitative analysis examination, determining vitamin C levels and determining antioxidant activity using the DPPH method with a UV-Vis spectrophotometer. The results of the study showed that the levels of vitamin C in the squeezed crystal guava flesh were 0.59441 ± 0.00032 mg/g and in the squeezed crystal guava seeds 0.32062 ± 0.00064 mg/g. While the antioxidant activity with the IC50 results of the squeezed crystal guava flesh was 3751.3274 µg/mL in the squeezed crystal guava seeds 2785.2941 µg/mL and as a comparison, vitamin C with IC50 was 4.2539 µg/mL. It can be concluded that the levels of vitamin C in the squeezed crystal guava flesh were higher than in the squeezed crystal guava seeds. The strength of the antioxidant activity was very weak because the sample used was a squeeze obtained by filtering using flannel cloth.